Multi-omics analysis reveals the molecular changes accompanying heavy-grazing-induced dwarfing of Stipa grandis - Wan, Dongli; Wan, Yongqing; Zhang, Tongrui; Wang, Ruigang; Ding, Yong (Frontiers in Plant Science, 2022)
Heavy grazing significantly reduces Stipa grandis growth. To enhance our understanding of plant responses to heavy grazing, in this study transcriptomic, proteomic, and metabolic analyses of the leaves of non-grazed plants (NG) and heavy-grazing-induced dwarf plants (HG) of S. grandis were conducted. A total of 101 metabolites, 167 proteins, and 1268 genes differed in abundance between the HG and NG groups. Analysis of Kyoto Encyclopedia of Genes and Genomes pathways among differentially accumulated metabolites (DAMs) revealed that the most enriched pathways were flavone and flavonol biosynthesis, tryptophan metabolism, and phenylpropanoid biosynthesis. An integrative analysis of differentially expressed genes and proteins, and DAMs in these three pathways was performed. Heavy-grazing-induced dwarfism decreased the accumulation of DAMs enriched in phenylpropanoid biosynthesis, among which four DAMs were associated with lignin biosynthesis. In contrast, all DAMs enriched in flavone and flavonol biosynthesis and tryptophan metabolism showed increased accumulation in HG compared with NG plants. Among the DAMS enriched in tryptophan metabolism, three were involved in tryptophan-dependent IAA biosynthesis. Some of the differentially expressed genes and proteins enriched in these pathways showed different expression trends. The results indicated that these pathways play important roles in the regulation of growth and grazing-associated stress adaption of S. grandis. This study enriches knowledge of the mechanism of heavy-grazing-induced growth inhibition of S. grandis and provides valuable information for restoration of the productivity in degraded grassland.